Social Participation in Health 2.0 - Hesse, Bradford W. (2010)
Computer scientists are working with biomedical researchers, policy specialists, and medical practitioners to usher in a new era in healthcare. A recently convened panel of experts considered various research opportunities for technology-mediated social participation in Health 2.0.